Part I: Hydrological properties within the eastern Indonesian throughflow region during the INDOMIX experiment. (April 2022) - Atmadipoera, Agus S.; Koch-Larrouy, Ariane; Madec, Gurvan; Grelet, Jacques; Baurand, François; Jaya, Indra; Dadou, Isabelle
Abstract: The Indonesian Mixing (INDOMIX) cruise of July 2010, resolves the Pacific Ocean water masses spreading from the Halmahera Sea through the Seram Sea, Manipa Strait, Banda Sea, to the Ombai Strait, and along the southern margin of Lesser Sunda Arc across the northern Savu Sea, Sumba Strait, and south of Lombok Strait. This paper focuses on the characteristics and stratification of the water masses, along this path and Part II of this study discusses the biogeochemical aspects. Two companion papers on quantification of turbulent mixing have been published elsewhere. We find: a) A marked transformation of South Pacific (SP) thermocline water within a sharp salinity front between the Halmahera Seram Seas. Tidally induced vertical mixing is the main process weakening the SP stratification, as suggested by a simple 1-dimensional diffusion model forced by vertical diffusivity of INDOMIX vertical microstructure profiler dataset. The transformation of SP water by vertical mixing can occur after 3 days, which is in good agreement with previously reported water mass residence times. Lateral advection plays a minor role; b) Interleaving salinity structure within the thermocline of the central Halmahera Sea and two deeper inflow channels. The interleaving salinity features within the central Halmahera Sea thermocline occurs where vertical diffusivity is relatively weak, compared to the vertical mixing at entry/exit portal that removes the interleaving salinity features. Two deeper inflow channels (about 950 m and 740 m depth) in the entry portal of the Halmahera Sea are mapped from the multi-beam echo sounder measurement, where both channels allow the renewal of SP thermocline water and salinity interleaving processes; c) Northward flow of thermocline water (100–200 m depth) in the Manipa Strait that injects Banda homogeneous salinity water into Seram Sea that erode Halmahera salty water via strong diapycnal mixing; d) Cyclonic upper layer circulation in Banda where eastward (westward) flow occurs in the northern (southern) Banda, confirmed by recent modeling study; and e) Relative salty Indian Ocean intermediate water flowing along southern margin of the Lesser Sunda Arc, within the South Java Undercurrent. Two distinct upper thermocline water, due to different source of Indonesian Throughflow (ITF) water, are found in the Banda Sea: fresher and colder water contrasting to saltier and warmer water that converge in this confluence region. Beneath it, Banda intermediate homogeneous salinity water and low dissolved oxygen water is dominant. Highlights: The INDOMIX cruise dataset resolve the Pacific Ocean water masses spreading in the eastern Indonesian Throughflow region. Strong transformation of South Pacific (SP) thermocline water front is found between the Halmahera and Seram seas. Tidally induced vertical mixing is the main processs of extinction of SP stratification, as suggested by the diffusion model. Interleaving salinity structure in the central Halmahera Sea is related to a weak vertical diffusivity and renewal SP water. North Indian Intermediate Water flowing along southern margin of the Lesser Sunda Arc within the South Java Undercurrent.